Current and future forage suitability maps for Ethiopia and Kenya - Mutua, John Y.; Notenbaert, An Maria Omer (International Center for Tropical Agriculture, 2019)
This data was produced using Targeting Tools – a web-based GIS tool, which matches a suitability criteria that include climate and environmental requirements for each of the forage varieties with a spatial database that’s comprises organic carbon, soil PH, annual precipitation, mean temperature, growing days and elevation data to characterize the suitability.